2009
DOI: 10.1002/jcb.22384
|View full text |Cite
|
Sign up to set email alerts
|

BBR induces apoptosis in HepG2 cell through an Akt‐ASK1‐ROS‐p38MAPKs‐linked cascade

Abstract: Berberine (BBR) has indicated significant antimicrobial activity against a variety of organisms including bacteria, viruses, and fungi. The mechanism by which BBR initiates apoptosis remains poorly understood. In the present study, we demonstrated that BBR exhibited significant cytotoxicity in human hepatoma HepG2 cells. Herein, we investigated cytotoxicity mechanism of BBR in HepG2 cells. The results showed that the induction of apoptosis in HepG2 cells by BBR was characterized by DNA fragmentation, an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…It was reported that BBR induced the ROS-mediated apoptosis and downregulated the expression of Bcl-2 protein in HepG2 cells, which were prevented by NAC treatment (17). We also found that treatment with BBR induced ROS generation and that pretreatment with NAC prevented BBR plus TRAIL-induced apoptosis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It was reported that BBR induced the ROS-mediated apoptosis and downregulated the expression of Bcl-2 protein in HepG2 cells, which were prevented by NAC treatment (17). We also found that treatment with BBR induced ROS generation and that pretreatment with NAC prevented BBR plus TRAIL-induced apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that BBR increases ROS production in various cancer cells (10,17,18). Therefore, we examined whether ROS generation might be involved in BBR plus TRAILinduced apoptosis.…”
Section: Bbr-stimulated Trail-induced Apoptosis Appears To Be Dependementioning
confidence: 99%
“…Studies have found that Akt and ROS could interact with each other in the pathway. 32,42,43 We have shown here that the decrease of Akt activity is regulated by ROS generation in the tetrandrine-induced HCC cell apoptosis (Fig. 5).…”
Section: Discussionmentioning
confidence: 57%
“…Studies have reported AKT activation can increase production of intracellular ROS in apoptosis induction and that ROS generation could repress AKT signaling [32,33]. To investigate the relationship between ROS generation and AKT inhibition in combination treatment-induced apoptosis, western blot analyses were carried out to examine AKT activity in the presence of the ROS scavenger NAC.…”
Section: Combination Treatment-induced Apoptosis Of Pc Cells Via Inacmentioning
confidence: 99%